Exploration-Exploitation tradeoffs and information-knowledge gaps in self-regulated learning: Implications for training and development - Hardy,Jay; Day,Eric A.; Arthur Jr,Winfred (Human Resource Management Review, 2019)
Learning in modern organizations often involves managing a tradeoff between exploration (i.e., knowledge expansion) and exploitation (i.e., knowledge refinement). In this paper, we consider the implications of this tradeoff in the context of learner-controlled training and development. We then propose a model that integrates research on control theory, curiosity, and skill acquisition to explain how information knowledge gaps (i.e., gaps between what learners believe they know and what they desire to know) guide resource allocation decisions throughout the learning process. Using this model, we present testable propositions regarding (a) the different approaches learners take when resolving exploration-exploitation tradeoffs, (b) how systematic changes in learner perceptions translate into changes in systematic learner behavior, and (c) how common biases in key learner perceptions can undermine the functioning of self-regulated learning in training and development contexts. We finish with a discussion of the model's implications for the science and practice of training and development.
Keywords: Management